An Investigation into Critical Thinking and Creative Thinking Skills for Science Pre-service Teacher in Fluid Mechanics Course - Diniya, Diniya; Muslim, Muslim; Rusdiana, Dadi; Hermita, Neni; Wijaya, Tommy Tanu; Oshima, Ryugo (IJIS Edu : Indonesian Journal of Integrated Science Education, 2024)
Nowadays, learning is designed to train 21st century skills so that they can keep up with the times. There are several skills that must be taught and one of the categories is the way of thinking including creativity, innovation, critical thinking, problem solving, and decision making. This study aims to examine the critical and creative thinking skills of prospective science teachers. The research method used is descriptive quantitative. The sample in this study amounted to 46 science pre-service teacher. The instrument used is a test question based on indicators of critical and creative thinking skills. Critical thinking questions in the form of essay questions amounted to 5 questions and creative thinking questions in the form of essay questions as many as 4 questions. The results demonstrate that critical thinking skills of science pre-service teacher in the reasoning and thinking as hypothesis testing indicators are in the fair category. For indicators of likelihood and uncertainty analysis and argument analysis are in the poor category while for indicators of problem-solving and decision making are in the very poor category. Science pre-service teacher creative thinking skills are in the very poor category for each indicator.